Multiresidue Methods for the Determination of Organic Micropollutants and Their Metabolites in Fish Matrices. (26th July 2019) - Molbert, Noëlie; Alliot, Fabrice; Santos, Raphaël; Chevreuil, Marc; Mouchel, Jean‐Marie; Goutte, Aurélie
Abstract: Two analytical methods were developed for the determination of 48 organic compounds and 20 of their main by‐products in fish matrices. The targeted compounds belong to various chemical classes of metabolizable (phthalates, polycyclic aromatic hydrocarbons, insecticides [pyrethroids and N, N ‐diethyl‐meta‐toluamide]) and legacy (organochlorine pesticides, polychlorinated biphenyls, polybrominated diphenyl ethers) pollutants. Analyses were performed by gas and liquid chromatography–tandem mass spectrometry in multiple reaction monitoring (MRM) and dynamic MRM, respectively. Method performances were satisfactory, with results meeting the validation criteria because they achieved good linearity responses, recovery, precision, and accuracy for most of the 68 investigated compounds. The methods were then applied on 3 feral chub ( Squalius cephalus ) collected from the Marne hydrographic network (France). Twenty‐six parent compounds and 5 metabolites were systematically detected in fish matrices, with substantial concentration variability within and among individuals. Phthalates and pyrethroids accounted for most of the pollutant load. Metabolite concentrations in liver samples exceeded those of parent molecules in fish muscle. The present study presents 2 reliable methods for the determination of a wide range of contaminants and underlines the importance of metabolite analysis for a more comprehensive understanding of pollutant bioaccumulation and fate in aquatic organisms. Environ Toxicol Chem 2019;38:1866–1878. © 2019 SETAC. Abstract : Two analytical procedures were developed for the determination of organic pollutants and their by‐products in fish matrices by GC‐MS/MS and LC‐MS/MS analyses, respectively.